p53 Mutants Have Selective Dominant-Negative Effects on Apoptosis but Not Growth Arrest in Human Cancer Cell Lines - Aurelio, Oscar N. (American Society for Microbiology, 2000)
A bidirectional expression vector that allowed equal transcription of cloned wild-type and mutant p53 cDNAs from the same vector was developed. The vector was transfected into CaLu 6 lung carcinoma cells or Saos-2 osteosarcoma cells. All p53 mutants examined were recessive to wild-type p53 transactivation of p21(WAF1/CIP1) but dominant-negative for transactivation of Bax. An examination of effects on growth arrest and apoptotic pathways indicated that all mutants were recessive to wild type for growth arrest but only three of seven mutants were dominant negative for induction of apoptosis.